2011
DOI: 10.1002/pssr.201105489
|View full text |Cite
|
Sign up to set email alerts
|

Visible emission from ZnCdO/ZnO multiple quantum wells

Abstract: Due to the large demand for optoelectronic devices covering the spectral range from green to ultraviolet, extensive research has been triggered into wide-bandgap group III-nitride semiconductors. Since InGaN-based devices exhibit a strong decrease in efficiency advancing the green spectral region [1], ZnO-based devices are a promising alternative.An emission energy in the visible spectral range was obtained in e.g. Zn 1-x Cd x O/ZnO quantum wells (QWs) or double heterostructures [2,3]. Large Cd contents up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 9 publications
1
12
0
7
Order By: Relevance
“…(See Figure a.) The energy of the QW-related emission was tuned in almost the entire range between the emission energy of the barrier material and the bulk emission energy of the QW material of 2.46 eV . The luminescence of the (Mg,Zn)O barrier layer is observed at an energy of ∼3.45 eV corresponding to a Mg content of 0.075.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(See Figure a.) The energy of the QW-related emission was tuned in almost the entire range between the emission energy of the barrier material and the bulk emission energy of the QW material of 2.46 eV . The luminescence of the (Mg,Zn)O barrier layer is observed at an energy of ∼3.45 eV corresponding to a Mg content of 0.075.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The NWs direct toward the plasma plume, and the substrate rotates for a better homogeneity of the coating process. To obtain a large Cd content in the QWs, the NWs were held at a temperature of ∼300 °C . Oxygen partial pressures of 2.6 Pa for (Zn,Cd)O and 0.2 Pa for (Mg,Zn)O were applied, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al [12] obtained the band-edge green electroluminescence (EL) at 500 nm from Zn 0.80 Cd 0.20 O/Zn 0.92 Cd 0.08 O multiple quantum-well light-emitting diodes (LEDs) on p-type 4H-SiC substrates. The change of the emission energy from the green to the violet spectral range (2.5 eV to 3.1 eV) by tuning the quantum well thickness was observed by Lange et al [13]. Thus, the optical performance of ZnO-based devices and heterostructures is strongly governed by the phenomena occurring in the Zn 1-x Cd x O layer.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, several groups have studied the properties of Zn 1-x Cd x O/ZnO QWs [10][11][12][13]. Liu et al [10] observed the increase of the spontaneous emission rate from Zn 1-x Cd x O QWs by surface plasmon coupling.…”
Section: Introductionmentioning
confidence: 99%